2014
DOI: 10.1001/jamainternmed.2014.4193
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Publicly Available Scientific Evidence on the Safety and Effectiveness of Implanted Medical Devices

Abstract: IMPORTANCE Under the 510(k) process, the US Food and Drug Administration (FDA) clears about 400 implanted medical devices that are considered moderate to high risk for market each year without requiring clinical testing. Instead, the FDA requires the applicant to provide scientific evidence that the new device is "substantially equivalent" to a device or devices already on the market (predicate devices). Companies are legally required to submit the evidence to the FDA and to make publicly available at least a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 4 publications
1
68
0
2
Order By: Relevance
“…For all those high‐risk recalls that satisfied those criteria and also for moderate‐risk recalled EMRs, we used the FDA's databases to determine the type of testing used as the basis of the FDA's regulatory determinations that allowed the devices to go on the market. This included reviewing any relevant data or testing information described in device companies’ 510(k) publicly available summaries, as described in an earlier study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all those high‐risk recalls that satisfied those criteria and also for moderate‐risk recalled EMRs, we used the FDA's databases to determine the type of testing used as the basis of the FDA's regulatory determinations that allowed the devices to go on the market. This included reviewing any relevant data or testing information described in device companies’ 510(k) publicly available summaries, as described in an earlier study …”
Section: Methodsmentioning
confidence: 99%
“…Premarket approval (PMA), the FDA's most stringent review process for devices, applies to software posing the greatest risk to patient safety and requires the manufacturer to provide clear evidence of safety and effectiveness. In contrast, products expected to pose less risk to patients, and thus go through the 510(k) review process, are not required to be proven safe, effective, or accurate but instead must demonstrate that they are similar to a product already sold in the United States in order to be cleared for market by the FDA …”
Section: Fda Medical Device Regulatory Categoriesmentioning
confidence: 99%
“…Large investments in research are being made by several stakeholders, including the European Union (www.medtechta.eu/wps/wcm/connect/Site/MedtecHTA/Home, www.adhophta.eu and www.advance-hta.eu), to deepen our knowledge on current methods for assessing medical devices, especially dealing with clinical evidence. The debate on regulation of medical devices has very often focussed on the type and role of clinical evidence [3,[34][35][36]. Clinical evidence for medical devices is often more challenging to collect through traditional experimental studies such as RCTs and, although RCTs rank high in terms of internal validity, other sources of data can be relevant and reliable to take policy decisions [37], especially when the adoption and diffusion of new devices largely precede any RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite public disclosure laws, the scientific basis for determining substantial equivalence between predicate and newly approved devices is not always publically available or clearly described. 1 As consumers of power morcellators, we searched the FDA web site (http://www.fda.gov/MedicalDevices) to identify their predicate devices. Through a series of "substantially equivalent" devices, the Internet trail ends at the Cook Tissue Morcellator, approved in 1991.…”
mentioning
confidence: 99%
“…3 Many recalls of devices deemed "moderate risk" and approved through the 510(k) process have been associated with major complications; the devices have posed more than a moderate risk to patients. 1 In 2011, an Institute of Medicine report concluded that the 510(k) pathway is fundamentally flawed and recommended that the FDA develop a new pre-and postapproval regulatory pathway to ensure patient safety. 4 The FDA has been working to respond to some of the concerns raised about their evaluation processes.…”
mentioning
confidence: 99%